Exploring engagement, well-being, and welfare on engagement platforms: Insight into the personal service sector from the DACH region - Simon Michalke; Lisa Lohrenz; Christoph Lattemann; Susanne Robra-Bissantz (Electronic Markets, 2022)
Engagement platforms (EPs) are an essential technology to enable co-creation and service innovation. Therefore, the design and governance of these platforms are receiving increasing attention in research. In this study, we aim to identify which activities and mechanisms foster engagement and which governance mechanisms are implemented to avoid harm on EPs. To this end, we conducted expert interviews with founders, CEOs, and managers of 14 personal and household-related service platform companies from the DACH region (Germany(D), Austria(A), Switzerland(CH)), to gain insights into their activities and mechanisms for creating and maintaining successful EPs. We found eight mechanisms, e.g., moderation of content, limitations of entry and certification, employed by personal EPs (PEPs) as self-regulatory mechanisms to avoid misconduct and negative experiences of actors. The identified governance mechanisms may guide the design and governing of PEPs by providing tangible examples to foster actor engagement while considering externalities on a societal and individual level.
Keywords: O330; 620; Platforms; Service logic; Engagement; Social welfare; Well-being; Engagement platforms